2008
DOI: 10.1093/ajcn/87.6.1914
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in dairy and related nutrient consumption among US adults and their association with obesity, central obesity, and the metabolic syndrome

Abstract: Various dairy products may have differential associations with metabolic disorders, including obesity. Ethnic differences in dairy consumption may explain in part the ethnic disparities in metabolic disorders in the US population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
220
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(246 citation statements)
references
References 67 publications
20
220
5
Order By: Relevance
“…51 --59 Some studies failed to find any relationship, 53,60,61 and one study showed inconsistent results based on the kind of dairy product. 62 Cross-sectional studies cannot reach a casual relationship; therefore, to detect a causal relationship one would need to look at cohort studies. Findings from cohort studies on the association of dairy intake and weight change are inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…51 --59 Some studies failed to find any relationship, 53,60,61 and one study showed inconsistent results based on the kind of dairy product. 62 Cross-sectional studies cannot reach a casual relationship; therefore, to detect a causal relationship one would need to look at cohort studies. Findings from cohort studies on the association of dairy intake and weight change are inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the preponderance of evidence, mostly in adults, indicates that milk intake is more likely to be associated with beneficial cardiometabolic outcomes [13], [39], [40] and [41]. Few studies have shown the beneficial effects of other dairy products [10], [36] and [42].…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies suggest a possible beneficial effect of milk and dairy product consumption in relation to individual components of the MetS, there is a need for additional studies to determine the relationship between milk and dairy product intake and risk of the MetS (71) . A study performed in an ethnic diverse US population revealed that the OR for MetS per one additional daily serving of yoghurt was 0·40 (95 % CI 0·18, 0·89), whereas the opposite was found for cheese (OR 1·16; 95 % CI 1·04, 1·29) in a cohort of 4519 men and women (72) . This beneficial association of yoghurt consumption was confirmed in children living in the USA using data from the National Health and Nutrition Examination Survey (NHANES) cohort (5124 children aged 2-18 years) (73) .…”
Section: The Metabolic Syndromementioning
confidence: 99%